Gender identities and the decision to return: the case of Rwandan refugee men and women in North Kivu, DRC - Taiwa, Karen Koraeny (My University, 2016)
Repatriation like any other form of migration is highly gendered. The objective of this research study is to analyze the gendered determinants of repatriation. I will explore various motivations for return and the general literature surrounding repatriation. My interest in the research was inspired by my experience working with Rwandan returnees where I encountered more female returnees than men. The other reason was the invocation of the cessation of Rwandan refugees on the 30th June 2013.The implication of the cessation meant to bring to closure to a close the refugee status of Rwandans who fled the country before 31st December 1998 and to find alternative status for those refugees still in need of international protection. An interesting observation is that despite this invocation by the end of 2013, the number of Rwandan refugees coming back did not increase as was expected. At the time of the interviews, the invocation of the cessation status of Rwandan refugees was a not an issue in the Democratic Republic of Congo (DRC). However, a meeting held on the 2nd of October 2015 came up with new deadlines for the implementation on the cessation clause. This research follows a mini-research for my Honours degree that I conducted in 2014 with Rwandan refugees residing in Johannesburg. This work however differs from my previous pilot study in Johannesburg in two ways; in contrast to this research paper, my interviews in Johannesburg involved Rwandan refugees who had not taken the decision to return to Rwanda. Additionally, the refugee profile in South Africa comprised mostly political asylum-seekers while Rwandan refugees hosted in the DRC (my current research location) are mostly those who fled during the 1994 genocide. Voluntary repatriation is a contested issue. In various instances, refugees feel obliged to return either through active promotion of repatriation, reduction of aid in refugee camps or appalling conditions in countries of asylum. What is also evident is the politics between the countries of asylum and origin and the uncomfortable position the United Nations High Commissioner for Refugees (UNHCR) finds itself as it seeks to ensure the voluntary character of repatriation as is stipulated by the 1969 OAU convention. The gendered approach taken in migration studies reveals renegotiation of gender relations and roles as a result of displacement. Although the role of women changes considerably; social expectations puts more pressure on men to provide and as the limited livelihood opportunities during displacement curtails their primary role as breadwinners. Gender mainstreaming is one of the approaches employed by the, UNHCR to ensure that women are not only involved in all aspects of planning and development but also in issues of peace and security. The literature on repatriation, suggests that women and men consider different factors in their decision to return; men’s main concern is security while women dwell more on working structures like hospitals and schools for their children. During fieldwork, the household emerged as an important unit for repatriation decision making. The research employed a qualitative design. The tools for data collection included semi-structured in-depth questions for Rwandan refugee participants in Goma and key informants from the UNHCR and their government counterpart in the repatriation exercise the Commission Nationale pour les Réfugiés (CNR). In addition, I engaged in an extensive secondary data search through journals, books, the internet, newspapers and policy documents. Thematic analysis was utilized to analyze the collected data. Based on the findings, it was evident that Rwandan refugee men and women put into consideration different aspects in their decision to return to Rwandan. Men focused mostly on security issues both in the DRC and Rwanda while women considered working structures like schools, hospitals and the hope of reclaiming their spouses’ land for the sake of the children. On the decision to return, single women took the decision on their own while in the case of married couples, the men came up with the idea and discussed it with their wives and children. A cross cutting theme between the interviewed Rwandan refugee men and women was the important function of social networks as a pull factor for return. Social networking was especially important in obtaining information about the specific areas in Rwanda and also acted as assurance for temporary accommodation upon return and therefore reducing the cost of return migration. Based on the findings, access to information for both men and women was not mentioned as a major challenge owing to advances in technology (radios, internet, and mobile phones) and the presence of social networks. Keywords (Returnee, Cessation Clause, Repatriation, Reintegration, Decision-making process, Gender, Identity, Social networking)
A thesis submitted to the Faculty of Humanities School of Social Sciences, University of Witwatersrand, Johannesburg, in partial fulfilment for the degree of Masters in Migration & Displacement. Johannesburg 2016
Keywords: Gender identity; Gender mainstreaming; Refugees--Rwanda; Refugees--Congo (Democratic Republic); Repatriation; Return migration